Strategies of Small Traders Facing Modern Minimarkets In Pontianak City - Khosiati, Risky; Syafira, Eka (Tujjar International Journal of Islamic Economics Development, 2024)
The purpose of this study is to identify the strategies used by small traders when competing with contemporary minimarkets in Pontianak City. This study uses a descriptive qualitative approach by collecting data through observation, documentation, and in-depth interviews with 10 small traders who have been operating for at least 3 years. The results of the study show that the presence of minimarkets has different effects on small traders. Grocery traders have experienced a 30-40% decline in turnover, while fresh produce traders have remained stable. Small traders have strong social relationships, personalized service, and transaction flexibility that modern minimarkets cannot match. The long-term survival strategies implemented include payment flexibility, personalized service, and the use of simple technology such as WhatsApp.